Formulasi Gel Ekstrak Arang Tempurung Kelapa dan Uji Sensitivitas Terhadap Bakteri Escherichia coli - Yogaswari, Dinya; Kurniawan, Kurniawan; Mujahid, Ikhsan; Ritma Dhanti, Kurnia (BIOEDUSCIENCE, 2024)
Background: Escherichia coli bacteria are normal flora bacteria in the human digestive tract that can turn into opportunistic pathogens and cause diarrhea, hemorrhagic colitis, and hemolytic uremic syndrome (HUS). The existence of this bacterial infection is generally treated with the use of antibiotics, which have been shown to cause resistance to the E. coli bacteria, so it is necessary to treat them using other methods, namely by using drugs derived from natural ingredients (herbal medicines) that contain antibacterial compounds such as charcoal extract. coconut shell. The purpose of this study was to obtain the most effective coconut shell charcoal extract gel formulation for inhibiting the growth of E. coli bacteria in vitro. Methods: The method used in this study was a true experimental post-test only control group with treatment at different gel concentrations of 3%, 6%, and 9% with repetition. Results: The results of the one-way ANOVA analysis test showed that the treatment given to several concentrations of coconut shell charcoal extract had a mean difference in the area of the inhibition zone for E. coli bacteria with a known significance value of 0.002 (p <0.05), so it was continued with the post-host LSD test, and the results of several groups show a significant value (p <0.05) marked with the notation (*). Conclusion: Based on the results of the study, it can be concluded that the gel formulation of coconut shell charcoal extract with a concentration of 3% is most effective in inhibiting the growth of E. coli bacteria in vitro.